(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effect of a wifi router on the accuracy of an electronic apex locator in determining root canal length under clinical conditions. Materials and methods: A prospective clinical study was conducted on 10 root canals undergoing endodontic treatment. Root canal length was measured using an electronic apex locator under three conditions: without a wifi router, with a wifi router placed 50 cm away from the device, and with a wifi router placed adjacent to the device (0 cm). The root canal length measured on periapical radiographs was used as the reference value. Data were analyzed using the Friedman test and Fisher’s exact test with a significance level of p < 0.05. Results: No statistically significant differences were found in the mean rank of root canal length measurements obtained with the electronic apex locator among the tested conditions (p > 0.05). The accuracy within the clinically acceptable range of ± 0.5 mm was 80% without electronic devices, 70% when the wifi router was placed 50 cm away, and 60% when the wifi router was placed adjacent to the device. These differences were not statistically significant. Conclusion: The presence of a wifi router does not significantly affect the clinical accuracy of electronic apex locators in determining root canal length under typical dental clinic conditions.